2005
DOI: 10.1016/s0002-9440(10)62269-9
|View full text |Cite
|
Sign up to set email alerts
|

Acidification of the Osteoclastic Resorption Compartment Provides Insight into the Coupling of Bone Formation to Bone Resorption

Abstract: Patients with defective osteoclastic acidification have increased numbers of osteoclasts, with decreased resorption, but bone formation that remains unchanged. We demonstrate that osteoclast survival is increased when acidification is impaired, and that impairment of acidification results in inhibition of bone resorption without inhibition of bone formation. We investigated the role of acidification in human osteoclastic resorption and life span in vitro using inhibitors of chloride channels (NS5818/ NS3696), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
96
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 45 publications
16
96
1
1
Order By: Relevance
“…The osteoclasts have an attenuated capacity to resorb the calcified bone matrix. This mechanism, at least partially, seems to have an auto-regulatory effect of calcium directly on osteoclast survival (63,66). However, other studies have also shown that release of transforming growth factor b from the bone matrix caused induction of osteoclast apoptosis (67) and thus also participates in this auto-regulatory control of osteoclast activity.…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 96%
See 2 more Smart Citations
“…The osteoclasts have an attenuated capacity to resorb the calcified bone matrix. This mechanism, at least partially, seems to have an auto-regulatory effect of calcium directly on osteoclast survival (63,66). However, other studies have also shown that release of transforming growth factor b from the bone matrix caused induction of osteoclast apoptosis (67) and thus also participates in this auto-regulatory control of osteoclast activity.…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 96%
“…Histomorphometric analyses of ADO and osteoclast-rich ARO patients showed increased numbers of very large osteoclasts in vivo (17,41). In vitro analyses showed that osteoclastogenesis was normal, both with respect to time frame and numbers of osteoclasts, and with respect to morphology (17,52,53,63,64). The underlying reason for the lack of bone resorption by these osteoclasts was shown to be reduced acid secretion into the resorption lacunae (52,53,63,64,65), an effect also seen in ClC-7-deficient mice (49).…”
Section: Analysis Of Osteoclasts From Ado Patientsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been proposed that CLCN7 inhibition could be used to treat osteoporosis. 64 However, increased bone formation has never been demonstrated so far in ADO II. Histomorphometry has evidenced normal bone-forming surfaces in very few patients with ADO II.…”
Section: Discussionmentioning
confidence: 99%
“…This fits in with the hypothesis that osteoclasts present on bone surfaces can synthesize molecules that directly stimulate bone formation. 64,65 Recently sphingosine-1-phosphate (S1P), among other factors secreted by osteoclasts, has been shown to stimulate osteoblast differentiation. 65 More recently, in mice deficient for CTSK, SPHK1 increased expression triggers an higher secretion of S1P by osteoclasts, which has been shown to be responsible for increased bone formation.…”
Section: Discussionmentioning
confidence: 99%